Providing a disease management plan upon patient discharge from hospital. A Literature Review - Narliotis, Georgios Palaiologos; Chatzina, Garifalia; Katsavochristou , Vlasia; Manthou, Panagiota (Health & Research Journal, 2025)
Background: Providing a post-hospital disease management plan is an important nursing approach for some patient groups in the elderly population. However, the features and needs of persons after hospitalization impact the effectiveness of care offered after they return home. This review examines the effectiveness of illness management plans during patient discharge. Method and Material: The review encompassed relevant studies published between 2017 and 2021, identified via targeted keyword searches in international databases(PubMed, Scopus, Evidence-Based Nursing, Clinical Evidence)and focused on previously hospitalized individuals aged 65 and above. Results: The results indicated that the majority of individuals over 65 discharged from healthcare institutions face adaptation issues upon returning home, due to specific characteristics developed or observed during hospitalization and the immediate post-hospital period. Notable examples include severe cognitive decline in 45.4%, lack of family support in 55.8%and social isolation in 48%. Implementing post-hospital disease management plans appears effective for patients with mild disorders (while 23.7% of individuals with severe disorders prefer standard nursing care). Additionally, these interventions, models, and designs can reduce readmission rates by 1.7% within 30 days of discharge and improve end-of-life care content (after six months, an improvement in the agreement rate between patients and family regarding end-of-life decisions was recorded). Conclusions: The disparity in treatment for the elderly population between healthcare facilities and the community highlights the necessity of establishing post-hospital disease management strategies to mitigate unexpected readmissions and improve end-of-life care.